Enzyme alkaline phosphatase (ALP) and acid phosphatase (ACP) levels in Gir cattle and Jaffarabadi buffaloes - PADODARA, R.J.and GAJBHIYE, P.U., NINAN JACOB1, ARYA, J.S (Indian Journal of Animal Production and Management, 2020)
Plasma Alkaline Phosphatase (ALP) and Acid Phosphatase (ACP) levels were determined using standard diagnostic kits in male and female Gir cattle and Jaffarabadi buffalo at different ages (1 wk to 36 months), lactation months (1m to 3m), non-lactating animals (pregnant and non-pregnant) and in bulls and castrated males. Significant (P < 0.05) effect of age was seen in all four groups studied for plasma alkaline phosphatase and acid phosphatase (except in Jaffarabadi males) activities. The activity differed significantly (P < 0.05) between different lactation months in Gir cows and Jaffarabadi buffaloes for ALP. The significant (P < 0.05) effect of lactation was seen only in Gir cows with respect to ACP activity. Significant (P < 0.05) differences were observed between non-lactating stages for ALP (in Gir cows) and ACP (in Jaffarabadi buffaloes) activities. The levels of ALP and ACP differed significantly (P < 0.05) between Gir bulls and castrated animals. The enzyme activities between the females and between the males of Gir and Jaffarabadi species varied significantly (P < 0.05) for both the enzymes studied. The effect of lactation between Gir cows and Jaffarabadi buffaloes was found significant (P < 0.05) at different months of lactation for both the enzymes. The activities between Gir and Jaffarabadi in the non-lactating group differed significantly for ACP (both pregnant and non-pregnant), and for ALP (in pregnant). The values between bulls of Gir and Jaffarabadi differed significantly (P < 0.05) for ALP and ACP activities.